Second language learning and cultural identity - Parker, Jerry (Journal of curriculum studies research, 2019)
The importance of the teaching of Louisiana Regional French language and culture as an academic subject has been debated by many scholars for decades. While some see it as a necessary dimension of a French course offered in the state of Louisiana, others see the dialect and culture as unreal, non-existent, and less prestigious than Parisian French. This article presents a rationale for offering Louisiana Regional French courses as equivalents to Parisian French in the post-secondary core curriculum in Louisiana colleges and universities.